De Biedermann por Andorra hasta Biografie. La obra dramática de Frisch en España - Acosta, Luis A. (Revista de Filología Alemana, 2002)
This paper dels with the reception in Spain of three works by Frisch (1911-1991), namely, Biedermann y los incendiarios (Biedermann und die Brandstifter), 1958, Andorra, 1961, and Biografía (Biografie), 1967. These three plays have been produced for the stage in Spain by professional or commercial companies. Both the reception and the interpretation of the plays are seen from the perspective of comparativist methodologies. One the one hand, the way in which critics in its native tongue considered them is taken into account; on the other hand careful attention is paid to the peculiar way in which these works were received in Spain as a direct consequence of specific literary, cultural and historical conditions. Conflation of these two disparate analyses has brought about a new form of understanding.